2017
DOI: 10.1080/07317115.2017.1395377
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Cultural and Family Values on Social Connectedness and Loneliness among Ethnic Minority Elders

Abstract: Findings highlight the importance of addressing familial expectations in programs aimed at alleviating loneliness among ethnic minority elders.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
27
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(27 citation statements)
references
References 61 publications
0
27
0
Order By: Relevance
“…Social connectedness is critical for healthy aging (Kohli et al, 2009; O’Rourke & Sidani, 2017; Yiengprugsawan et al, 2018), and Muslim immigrant women from diverse ethnocultural communities have reported social disconnected in older age (Diaz et al, 2019; Senzai & Bazian, 2013). This three-year CBPR project aims to: (a) identify the ways social connectedness influences the lives of Muslim older women; and (b) determine the risks and drivers of disconnectedness.…”
Section: Cbpr Case Studies With Immigrant Older Adultsmentioning
confidence: 99%
“…Social connectedness is critical for healthy aging (Kohli et al, 2009; O’Rourke & Sidani, 2017; Yiengprugsawan et al, 2018), and Muslim immigrant women from diverse ethnocultural communities have reported social disconnected in older age (Diaz et al, 2019; Senzai & Bazian, 2013). This three-year CBPR project aims to: (a) identify the ways social connectedness influences the lives of Muslim older women; and (b) determine the risks and drivers of disconnectedness.…”
Section: Cbpr Case Studies With Immigrant Older Adultsmentioning
confidence: 99%
“…In addition to understanding the family experience of life, health, and illness, knowing the family's social and cultural context helps professionals understand a family's stories. This is because culture has been shown to be a strong determinant of beliefs, meanings, and attitudes toward health and illness (Garcia Diaz, Savundranayagam, Kloseck, & Fitzsimmons, 2017). Therefore, it is important to consider cultural beliefs and social behavior when seeking to understand the meanings that family gives to a situation that causes suffering.…”
mentioning
confidence: 99%
“…ARSMA-II Scale 1 was used to measure acculturation [43][44][45] ; this instrument was specifically designed for the Mexican American population. The instrument has 30 items measured in a 5-point Likert scale ranging from 1 = not at all to 5 = almost/extremely often.…”
Section: Methodsmentioning
confidence: 99%